ECG Measurements to Emphasize Atrial Potentials Using Modified Limb Lead System - K, Manikandan; K, Mohanasundaram (International Journal of Engineering and Technology, 2018)
With the advancement in the field of Electrocardiology (ECG), the acquisition of electrical activity of the heart plays an important role in the diagnosis of various cardiovascular diseases. In general, this activity of conduction is acquired using Standard 12 Lead ECG system. Recently, a Modified Limb Lead system has been developed to study the atrial electrical activity for the diagnosis of atrial arrhythmias. The present study is to derive the normal limits of female subjects using Modified Limb Lead (MLL) system. This study was evaluated in 59 female subjects 19.52 ± 1 (Mean ± S.D) and is primarily involved to study atrial potentials with the use of precordial and modified limb lead position. In sinus rhythm female subjects, the P wave amplitude was 33.06 ± 21.18 µV and the Ta wave amplitude was 20.72 ± 18.16 µV. The P wave duration was 94.22 ± 10.64 ms, the Ta wave duration was 85.51 ± 17.49 ms. The results show that modifications in the limb electrode placement have significant effect on amplitudes and PR segment which may be of great importance for the assessment of atrial potentials.
Keywords: Atrial arrhythmias; Electro cardiology; Modified Limb Lead System; Sinus rhythm; Standard 12 Lead System.